2004
DOI: 10.1037/0033-295x.111.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving the Intensity of Light.

Abstract: The relationship between luminance (i.e., the photometric intensity of light) and its perception (i.e., sensations of lightness or brightness) has long been a puzzle. In addition to the mystery of why these perceptual qualities do not scale with luminance in any simple way, "illusions" such as simultaneous brightness contrast, Mach bands, Craik-O'Brien-Cornsweet edge effects, and the Chubb-Sperling-Solomon illusion have all generated much interest but no generally accepted explanation. The authors review evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 48 publications
1
69
1
1
Order By: Relevance
“…Objects that appear to sit in the shadow, or under a dark filter, must be, or have repeatedly turned out to be in the past (Purves et al, 2004), lighter than equiluminant objects sitting in the light, and are therefore seen as such. The right display of Figure 19 is at odds with this argument, and shows that the explanatory power of illumination discounting is, at best, inadequate (see also Bressan, 2003).…”
Section: Snake Illusion and The Shredded And Reversed Snakesmentioning
confidence: 99%
“…Objects that appear to sit in the shadow, or under a dark filter, must be, or have repeatedly turned out to be in the past (Purves et al, 2004), lighter than equiluminant objects sitting in the light, and are therefore seen as such. The right display of Figure 19 is at odds with this argument, and shows that the explanatory power of illumination discounting is, at best, inadequate (see also Bressan, 2003).…”
Section: Snake Illusion and The Shredded And Reversed Snakesmentioning
confidence: 99%
“…Where such independence is achieved, stimulus intensity does not contribute much to stimulus identity; for example, neither does brightness contribute appreciably to the visual identity of an object (e.g. colour) (Livingstone & Hubel 1988;Lotto & Purves 1999;Purves et al 2004), nor does loudness contribute to the auditory identity of a sound (e.g. frequency) (Zeng & Shannon 1994;Escabi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A central puzzle in understanding how such percepts are generated by the visual system is that brightness does not correspond in any simple way to luminance. Thus, the same amount of light arising from a given region in a scene can elicit dramatically different brightness percepts when presented in different contexts (1,2) (Fig. 1).…”
mentioning
confidence: 99%
“…A growing body of evidence has shown that the visual system uses the statistics of stimulus features in natural environments to generate the visual percepts of the physical world (15); if so, the visual system must incorporate these statistics as a central feature of processing relevant to brightness and other visual qualia (2). Accordingly, we suppose that the perceived brightness elicited by the luminance of a target in any given context is based on the value of the target luminance in the probability distribution function of the possible values that co-occur with that contextual luminance experienced during evolution.…”
mentioning
confidence: 99%